1982
DOI: 10.1016/0304-3959(82)90022-7
|View full text |Cite
|
Sign up to set email alerts
|

A correlative anatomical and clinical study of pain suppression by deep brain stimulation

Abstract: The clinical results of electrical stimulation in medial thalamic regions for cancer pain have been correlated with the exact location of the stimulation sites. Five brains were examined by post-mortem histology. Chronic implantation of enamel coated platinum-iridium electrodes for up to 17 months caused relatively mild glial and neuronal reactions and no significant haemorrhage or infarction. The anatomical verifications showed that the electrodes were close to, but not exactly in, the regions defined by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 12 publications
1
45
0
Order By: Relevance
“…4) level, we observed areas of activation within the brainstem, the locality of which correlate with regions known to be involved in pain processing in animals (Traub et al, 1996;Rodella et al, 1998;Millan, 2002;Monnikes et al, 2003) and human studies (Boivie and Meyerson, 1982;Baskin et al, 1986;Tracey et al, 2002). The spatial pattern of activation was very similar for visceral and somatic pain; however, greater quantitative bilateral NCF activity during visceral pain compared with somatic was found.…”
Section: Rvm: Dorsolateral Pons Correlation Of Activationmentioning
confidence: 69%
See 1 more Smart Citation
“…4) level, we observed areas of activation within the brainstem, the locality of which correlate with regions known to be involved in pain processing in animals (Traub et al, 1996;Rodella et al, 1998;Millan, 2002;Monnikes et al, 2003) and human studies (Boivie and Meyerson, 1982;Baskin et al, 1986;Tracey et al, 2002). The spatial pattern of activation was very similar for visceral and somatic pain; however, greater quantitative bilateral NCF activity during visceral pain compared with somatic was found.…”
Section: Rvm: Dorsolateral Pons Correlation Of Activationmentioning
confidence: 69%
“…In a pivotal study, Reynolds (1969) highlighted the role of the periaqueductal gray (PAG) in the nocifensive response: electrical stimulation of the PAG in rats allowed abdominal surgery without the use of general anesthesia. This inhibition of the normal pain response through stimulation of discrete brainstem centers such as the PAG [stimulus-produced analgesia (SPA)] was subsequently described in humans (Boivie and Meyerson, 1982;Baskin et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis arose from animal experiments that revealed that stimulation produced analgesia reversed by naloxone [123,124], and human studies that also showed elevated levels of cerebrospinal fluid enkephalins and endorphins with DBS [18,125,126]. However, the cerebrospinal fluid measures were artifactual [127,128], and double blinded investigation in humans has revealed no cross-tolerance between DBS and morphine and similar reversibility between naloxone and saline placebo [129], confirming others' findings [33,130]. Our human naloxone studies suggest that only dorsal PAG/periventricular gray DBS may be acting via opioidergic mechanisms [131].…”
Section: Physiologymentioning
confidence: 55%
“…Several others pioneered thalamic DBS, including Mazars [24][25][26][27] and Adams who, along with Hosobuchi, also targeted the internal capsule [28][29][30]. Observations from inadvertent localization errors and investigations into current spread from the PAG led others to target more medial thalamic nuclei, including the centromedian-parafascicular complex (Cm-Pf) [31][32][33][34]. The rostral anterior cingulate cortex (Cg24) was recently targeted for DBS on the basis of functional neuroimaging demonstrating its activation and half a century of its lesioning by cingulotomy in cancer pain [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…35;36 It was later shown that this pain relief could also be produced in chronic pain patients. 37 The descending pain inhibitory tracts in the spinal cord seemed to originate in neurones in the nucleus raphe magnus (NRM). These neurones project to the dorsal horn and use serotonin as the principal neurotransmitter.…”
Section: Descending Pain Inhibitory and Facilitating Systemsmentioning
confidence: 99%